Análise da eficiência dos docentes de uma instituição federal de ensino superior - Lima, Gutierrez Araújo de (Universidade Federal Rural do Semi-Árido, 2020)
With the increase in federal higher education institutions in recent years, there is a need to assess the responsibility for the delivery of teaching, research and extension of these institutions, which may end up raising questions about whether, in practice, the teachers of the institutions are committed to fulfillment of their duty, in accordance with Ordinance No. 17, of May 11, 2016. So, this work aims to analyze the departments and their teaching staff of a federal institution of higher education that is present on a campus outside the headquarters, located in the municipality of Angicos-RN. The research instrument used for the development of this work began with SIGAA, where data were collected regarding the names of the teachers and their respective department, as well as the quantity and which disciplines are taught and the course of action. From there, the parameters to be analyzed were defined and later with the aid of the lattes curriculum, which is a platform that gathers information from researchers from all over the Brazilian territory, data were collected regarding the qualifications of teachers, status, research projects and extension, publications in journals and congresses, books, book chapters and the number of patents, where these data were gathered in spreadsheets in Excel that were later analyzed. Through a research with a quantitative approach, statistical techniques were applied, such as descriptive analysis, inference of the collected data, and application of multicriteria analysis using the ELECTRE I model, which involves multicriteria analysis. Suggestions were raised to improve the departments of the institution. higher education under study. The results gave an overview of the best teachers in their respective departments, where it can be highlighted that a large minority of teachers are responsible for all activities aimed at teaching research and extension.
Monografia
Keywords: Ensino; Pesquisa; Extensão; Eficiência; Multicritério; ELECTRE I; Teaching; Search; Extension; Efficiency; Multicriteria; ELECTRE; ENGENHARIAS::ENGENHARIA DE PRODUCAO